The Influence of Taste, Amenities and Price Perception to Increase Repeat Purchases at Mie Gacoan - Sari, Fitri Permata; Efendi,; Silitonga, Parlagutan (Technium Social Sciences Journal, 2026)
This study examines how taste, amenities, and price perception influence repeat purchase motivation among customers at Mie Gacoan, Condet Branch. Increasingly fierce competition in the culinary industry requires restaurants to understand what truly drives customers to return. This study employed a quantitative approach, involving 200 respondents who had purchased more than twice. Data were obtained through questionnaires and analyzed using SmartPLS 3. The results showed that price perception was the strongest factor influencing repeat purchase intention. Customers felt that the price offered was in line with the value they received, thus making them more likely to return. Taste also proved to have a positive effect, although its strength was not as strong as price perception. Meanwhile, restaurant amenities did not have a significant effect, indicating that the comfort of the place was not the main reason customers returned to Mie Gacoan Condet. Overall, these three variables were able to explain more than half of the variation in repeat purchase intention. These findings emphasize the importance of maintaining consistent taste and ensuring competitive prices to maintain customer loyalty.